Inflammatory monocytes mediate control of acute alphavirus infection in mice - Haist, Kelsey C.; Burrack, Kristina S.; Davenport, Bennett J.; Morrison, Thomas E. (PLoS pathogens, 2017)
Chikungunya virus (CHIKV) and Ross River virus (RRV) are mosquito-transmitted alphaviruses that cause debilitating acute and chronic musculoskeletal disease. Monocytes are implicated in the pathogenesis of these infections; however, their specific roles are not well defined. To investigate the role of inflammatory Ly6ChiCCR2+ monocytes in alphavirus pathogenesis, we used CCR2-DTR transgenic mice, enabling depletion of these cells by administration of diptheria toxin (DT). DT-treated CCR2-DTR mice displayed more severe disease following CHIKV and RRV infection and had fewer Ly6Chi monocytes and NK cells in circulation and muscle tissue compared with DT-treated WT mice. Furthermore, depletion of CCR2+ or Gr1+ cells, but not NK cells or neutrophils alone, restored virulence and increased viral loads in mice infected with an RRV strain encoding attenuating mutations in nsP1 to levels detected in monocyte-depleted mice infected with fully virulent RRV. Disease severity and viral loads also were increased in DT-treated CCR2-DTR+;Rag1-/- mice infected with the nsP1 mutant virus, confirming that these effects are independent of adaptive immunity. Monocytes and macrophages sorted from muscle tissue of RRV-infected mice were viral RNA positive and had elevated expression of Irf7, and co-culture of Ly6Chi monocytes with RRV-infected cells resulted in induction of type I IFN gene expression in monocytes that was Irf3;Irf7 and Mavs-dependent. Consistent with these data, viral loads of the attenuated nsP1 mutant virus were equivalent to those of WT RRV in Mavs-/- mice. Finally, reconstitution of Irf3-/-;Irf7-/- mice with CCR2-DTR bone marrow rescued mice from severe infection, and this effect was reversed by depletion of CCR2+ cells, indicating that CCR2+ hematopoietic cells are capable of inducing an antiviral response. Collectively, these data suggest that MAVS-dependent production of type I IFN by monocytes is critical for control of acute alphavirus infection and that determinants in nsP1, the viral RNA capping protein, counteract this response.